2021
DOI: 10.3390/jcm10153213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ejaculatory Abstinence Interval on Sperm Parameters and Clinical Outcome of ART. A Systematic Review of the Literature

Abstract: Since the publication of the first edition of the WHO (World Health Organization) Laboratory Manual for the examination of Human Semen in 1980, the reference values of sperm parameters have been updated on four occasions. Currently and globally, most of the laboratories analyzing semen samples use the latest, 5th edition of the manual that recommends ejaculatory abstinence from two to seven days before producing the sample for examination. While this standardized interval of time facilitates the interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…There was no significant difference between the sociodemographic characteristics between the participants in both the clomiphene citrate and the letrozole arm of the study, with majority of the participants having infertility for less than 5 years. In other words, the 2 drugs resulted in significant improvement in both sperm count and motility, however, the improvement observed from letrozole group appeared to be more pronounced and the difference was statistically significant [18].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…There was no significant difference between the sociodemographic characteristics between the participants in both the clomiphene citrate and the letrozole arm of the study, with majority of the participants having infertility for less than 5 years. In other words, the 2 drugs resulted in significant improvement in both sperm count and motility, however, the improvement observed from letrozole group appeared to be more pronounced and the difference was statistically significant [18].…”
Section: Discussionmentioning
confidence: 79%
“…Written consent was obtained from each participant after explaining the purpose and objective of the study to them and confidentiality was maintained.All principles governing ethical conduct was taken into consideration. The principles of benevolence and non-maleficence were also adopted in dealing with the participants.An increase in semen count of 25% above the highest count before the intervention was regarded as significant improvement while an increase of 10% in motility above the highest value before the intervention will be regarded as significant improvement [18].…”
Section: Ethical Approval and Consentmentioning
confidence: 99%
“…On the other hand, the shortened time of abstinence could also improve semen quality and significantly reduce the DNA fragmentation rate. Most studies have demonstrated that a long period of abstinence may lead to lower normal morphology and DNA quality rates of sperm, while increased DNA fragmentation can reduce the rate of top embryos, induce embryo development arrest, and even lead to abortion[ 17 , 18 ]. Since the sperm to be used for ICSI are selected randomly, in patients with an increased DNA fragmentation rate, the possibility of selecting sperm with DNA breakage is also increased.…”
Section: Discussionmentioning
confidence: 99%
“…While the World Health Organization (WHO) currently recommends a 2- to 7-day abstinence period prior to a semen analysis [ 75 ], this interval is based largely on the need to standardize semen analysis results rather than on clinical outcomes [ 76 ]. This has prompted researchers to further investigate the optimal abstinence period for infertile men, including its relationship to sperm DNA fragmentation and impact on pregnancy and live birth rates.…”
Section: Methods For Overcoming High Sdfmentioning
confidence: 99%